2021
DOI: 10.2166/wpt.2021.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bridge piers shapes on the flow of the lower Yellow River

Abstract: The shape of bridge piers across rivers is one of the significant factors that affect the backwater in the river. The study on the influence of bridge piers shapes on the flow patterns of the river is valuable to the design of the bridge and river flooding. Based on the Mike 21 Flow Model hydrodynamic model, dynamic numerical simulations were conducted to investigate the effect of different shapes of bridge piers on water flow. The result shows that rectangular, circular and elliptical piers have water blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Different structure shapes result in different interaction areas and deflection directions, changing the deflection angle, mainstream velocity, and the water exchange rate. Existing studies have shown that pier diameter, shapes and other factors influence the flow field significantly [47,80,81]. The deflection angle that corresponds to the triangular prism and semi-cylinder is approximate and relatively small, generally about 30-45 • , while that for the rectangular column is larger, approximately 90 • for small l and decreases as l increases.…”
Section: Discussionmentioning
confidence: 99%
“…Different structure shapes result in different interaction areas and deflection directions, changing the deflection angle, mainstream velocity, and the water exchange rate. Existing studies have shown that pier diameter, shapes and other factors influence the flow field significantly [47,80,81]. The deflection angle that corresponds to the triangular prism and semi-cylinder is approximate and relatively small, generally about 30-45 • , while that for the rectangular column is larger, approximately 90 • for small l and decreases as l increases.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, scholars at home and abroad have conducted a large number of related studies on the impact of cross-river bridges on river channels and achieved more fruitful results. (David et al 2019) conducted a hydrological simulation assessment of long-term regional bridge scour risk based on physical climate change and applied it in the Lihay River basin; (Tewodros & Abdusselam 2019) used the MIKE21 FM model to assess the risk of bridge scour in the Ayama basin in Turkey modeled the effect of urbanization on flood risk in the Ayamama basin, Istanbul; (Costabile et al 2015) comparatively analyzed the backwater effects of bridge and no-bridge scenarios based on 1D and 2D river flood models; (Dimitriadis et al 2016) comparatively assessed the uncertainty in flood mapping based on 1D and quasi-2D hydraulic models; (Zhang et al 2021) based on MIKE21FM model, simulated the effect of different shaped piers on the flow regime of the river; (Echeverribar et al 2019) provided a robust two-dimensional model for simulating flood events, which has the ability to avoid instability and makes the model suitable for numerical correction of complex phenomenon simulations (Wang & Jing 2019) studied the effect of bridge piers on flood hazards in the Jialing River basin using the MIKE21 two-dimensional numerical model. (Liu et al 2020) based on a two-dimensional hydrodynamic model with dynamic numerical simulation of the congestion and scour generated by the current bridge and the bridge to be reconstructed; (Yan et al 2020) studied the pier front congestion and section average congestion characteristics of double piles under different diameter and flow velocity conditions based on the principle of momentum conservation and hydrodynamic model; (Yu & Zhu 2019) used the Reynolds time-averaged N-S equation and the standard k-ε turbulence model to investigate the local scour of a series of The local scour refinement of double-cylindrical piers was simulated using the Reynolds time-averaged N-S equation and standard k-ε turbulence model.…”
Section: Introductionmentioning
confidence: 99%